DISKURSUS ALIRAN TEORI BELAJAR UTAMA - Muhammad Komarudin; KM. Ridho El-Razy; Kasinyo Harto; Mardiah Astuti (Raudhah - Proud To Be Professional, 2023)
Learning is an important part of life. In essence, humans need to find out about something, and as long as humans still want to learn, that curiosity will always go hand in hand. In principle, when a person's learning process cannot be done individually. In the process towards understanding there must be a teacher. In the learning process, understandings or learning theories are needed so that an educator will more easily convey the material to be delivered. Learning theory is a method or strategy that can make it easier to teach. But based on the facts in the field there are still many teachers who prefer to convey knowledge based on experiences in teaching and learning. Teachers have produced effective ways to teach and transfer knowledge aimed at their students. Basically there are many learning theories, but only a few teachers or educators often use them. There are five learning theories, namely Information Process Flow learning theory, Behaviorism learning theory, cognitivism learning theory, constructivism learning theory, and humanism learning theory.